Market power, productivity and distribution of wages: Theory and evidence with micro data - Oleksandr Shepotylo; Volodymyr Vakhitov (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2020)
The declining labor share in national income and rising inequality over the last four decades raise questions about causes of these trends. In order to explain these trends, we develop a theoretical model that links intra-industry distribution of wages to variation in market power of firms. The model predicts that wages depend crucially on the demand side characteristics - they decline with market power if and only if demand elasticity is increasing with firm's output. Trade liberalization leads to expansion of more productive firms, which also increases their bargaining power, resulting in lower share of wage bill in total revenue. The model predictions are tested on a sample of Ukrainian manufacturing firms in 2001-2007. We document that an increase in firm's size increases its bargaining power relative to workers. We measure firm level markups, and show that they increase with firm's output and market size. We find that wage rises with firm's productivity, but fall with its market power. The results are robust to various model specifications estimated at the firm and industry levels.
urn:nbn:de:101:1-2020100511085614654070
Keywords: D43; F12; J31; 330; wage bargaining; wage inequality; heterogeneous firms; productivity; variablemarkups; international trade; monopolistic competition